2018
DOI: 10.1080/2162402x.2018.1554967
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor ligands induce TREM-1 expression on dendritic cells: analysis of their role in tumors

Abstract: Dendritic cells (DCs) initiate adaptive immune responses after their migration to secondary lymphoid organs. The LXR ligands/oxysterols and the RXR ligand 9-cis Retinoic Acid (9-cis RA) were shown to dampen DC migration to lymphoid organs through the inhibition of CCR7 expression. We performed transcriptomics of DCs undergoing maturation in the presence of the LXR ligand 22R-Hydroxycholesterol (22R-HC). The analysis highlighted more than 1500 genes modulated by 22R-HC treatment, including the triggering recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…While TREM1-associated neutrophils and macrophages contribute to the immune-escape and metastasis of tumors, aberrant expression of TREM1 is also found in tumor cells themselves as well as in established cell lines and provides growth, survival, and migration advantages 44 . It has also been shown that in non-myeloid cells, TREM1 expression can be induced by nuclear receptor ligands 45 .…”
Section: Discussionmentioning
confidence: 99%
“…While TREM1-associated neutrophils and macrophages contribute to the immune-escape and metastasis of tumors, aberrant expression of TREM1 is also found in tumor cells themselves as well as in established cell lines and provides growth, survival, and migration advantages 44 . It has also been shown that in non-myeloid cells, TREM1 expression can be induced by nuclear receptor ligands 45 .…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 involvement in NSCLC progression was further demonstrated by the finding that TREM-1 engagement by an agonist mAb in macrophages increased NSCLC's cell invasive ability, which was suppressed upon TREM-1 inhibition by shRNA [221]. TREM-1+ DCs accumulation in pleural effusions from patients with lung adenocarcinoma also seems to be associated with disease aggressiveness and bad prognosis [223].…”
Section: Trem-1 Role In Cancermentioning
confidence: 97%
“…The GF9 peptide also attenuated tumour growth and prolonged survival in a model of pancreatic cancer 71 . Although TREM1 is mainly expressed in granulocytes and macrophages, it has been shown that TREM1 is induced in tumour-associated DCs through activation of the nuclear receptors RXR, RAR, LXR and VDR 72 . In patients with cancer, TREM1 was found in DCs from pleural effusions and ascites, which contain the LXR ligands such as oxysterols and the RXR ligand such as 9-cis retinoic acid; moreover, in vitro exposure of monocyte-derived DCs to tumour-conditioned fluids induced the expression of TREM1 together with LXR and RAR target genes.…”
Section: Trem1 Contributes To Cancer Inflammationmentioning
confidence: 99%